2000
DOI: 10.1007/s004250000270
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency-induced phytosiderophore release by the Triticaceae is not consistently expressed in solution culture

Abstract: The effects of zinc (Zn) and iron (Fe) deficiencies on phytosiderophore (PS) exudation by three barley (Hordeum vulgare L.) cultivars differing in Zn efficiency were assessed using chelator-buffered nutrient solutions. A similar study was carried out with four wheat (Triticum aestivum L. and T. durum Desf.) cultivars, including the Zn-efficient Aroona and Zn-inefficient Durati. Despite severe Zn deficiency, none of the barley or wheat cultivars studied exhibited significantly elevated PS release rates, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 36 publications
1
48
0
1
Order By: Relevance
“…Plants were grown in a chelator-buffered nutrient solution consisting of macro-and micronutrients detailed in Table 1 and exposed to As concentrations of 6.7 µM As(III) i for six weeks. The nutrient solution was buffered with 2-(N-morpholino)ethanesulfonic acid (MES) adjusted to a pH of 6.5, and contained 57.7 µM HEDTA (2-hydroxyethyl)ethylenediaminetriacetic acid), which is a 27.7 molar excess of the sum of micronutrients [42,43]. Nutrient solutions were changed every 3-5 days, with more frequent changes as the plants grew larger.…”
Section: Hydroponic Experiments and Root Sectioningmentioning
confidence: 99%
“…Plants were grown in a chelator-buffered nutrient solution consisting of macro-and micronutrients detailed in Table 1 and exposed to As concentrations of 6.7 µM As(III) i for six weeks. The nutrient solution was buffered with 2-(N-morpholino)ethanesulfonic acid (MES) adjusted to a pH of 6.5, and contained 57.7 µM HEDTA (2-hydroxyethyl)ethylenediaminetriacetic acid), which is a 27.7 molar excess of the sum of micronutrients [42,43]. Nutrient solutions were changed every 3-5 days, with more frequent changes as the plants grew larger.…”
Section: Hydroponic Experiments and Root Sectioningmentioning
confidence: 99%
“…Potassium fertilization either applied on foliage or soil, cope the drought stress and consequently decreases the transpiration rate of crop plants (Zareian et al, 2013). Pedler et al (2000) resulted that zinc application increases the CGR and might be due to the role of zinc in bio-synthesis of tryptophan, a precursor of auxin hormone and mainly responsible for rapid growth rate. Application of potassium and zinc fertilizers either on soil or foliage showed that NAR had a positive linear relationship with potassium fertilizers (Szewczuk et al, 2009;Nadim et al, 2012).…”
Section: Figmentioning
confidence: 99%
“…In fact, zinc is essential for tryptophan synthesis, which is a prerequisite for auxin formation, therefore amount of auxin decreases by zinc deficiency (Marschner, 1995 andPedler et al, 2000). Zinc is the main building part of some enzymes and is needed for the plant enzymes formation of most species.…”
Section: Foliage Charactersmentioning
confidence: 99%
“…Zinc is the main building part of some enzymes and is needed for the plant enzymes formation of most species. In addition, many enzymatic reactions be active by zinc (Vitosh et al, 1994, Pedler et al, 2000and Akay, 2011. Table 4 demonstrate the effect of conducted treatments on the pear tree yield (Kg.).…”
Section: Foliage Charactersmentioning
confidence: 99%